Determining The Agricultural Drought and Desertification Intensity in Diyala Province / Iraq Using Sentinel-2 images - Hadid, Rana S.; Ahmed, Bushra A. (Iraqi Journal of Science, 2024)
Desertification is the deterioration of land brought on by human activity, climate change, and a loss of vegetation cover and biodiversity. This paper assesses the agricultural drought and desertification levels of Khanaqin district in Diyala province, Iraq, using Sentinel-2 images with a high resolution of 10 m between July 22, 2016, and July 22, 2022. The Modified Soil-Adjusted Vegetation Index (MSAVI2), Topsoil Grain Size Index (TGSI), and Salinity Index (SI) derived from Sentinel-2 satellite images were used for this aim. The result showed that the area covered by low desertification intensity increased from (12.05%-9.41%) for the years (2016-2022). The area covered by high desertification intensity increased from (32.49-36.44% for the years (2016-2022), indicating an accelerated desertification process. Finally, the area covered by high desertification intensity increased from 12.34%-21.23% for years (2016-2022). Natural climate variability and human activities, such as land use, overgrazing, deforestation, and unsustainable farming practices, cause agricultural drought and desertification.